Re-Os isotopic dating on molybdenite separates and its geological significance from the Yaojiagou molybdenum deposit, Liaoning Province - Fang JunQin; Nie FengJun; Zhang Ke; Liu Yong; Xu Bei (ACTA PETROLOGICA SINICA, 2012)
Eight molybdenite samples were selected from the Yaojiagou molybdenum deposit. The Re-Os isotopic model ages ranging from 166. 1 +/- 2. 3Ma to 169. 1 +/- 2. 5Ma, yielded an isochron age of 168.8 +/- 3. 9Ma (MSWD =1. 12), which was interpreted to be the ore-forming age of the deposit. Combined with existing geochronologic data of Yaojiagou granit pluton, we assume that there were multistage of intrusions in Yaojiagou area and the Yaojiagou molybdenum deposit was related to the magma intrusion activities in 168. 8 +/- 3. 9Ma. In combination with metallogenic geological background, we infer that the Yaojiagou molybdenum deposit developed from Early to Middle Jurassic, influenced by magma and fluid function of post-collision between North China Craton and Siberia Craton.